Analysis of Creativity and Attitudes Caring The Environment of Junior High School Students: Study of Environmental Physics Learning Using Learning Modules - Amelia, T.; Jumini, S.; Khoiri, A. (Jurnal Pendidikan Fisika Indonesia, 2021)
The natural and socio-cultural environment of the Wonosobo community has various potentials that can be explored and developed to support the science learning process. Pranotomongso is a form of culture used by farmers to cultivate nature. This study aims to determine the application of ethnoscience-based integrated science learning to foster environmental awareness and student creativity. This research is a quantitative study using the True Experimental method, with a Posttest Only Control Design, the sampling technique is random sampling. The instruments used for data collection were tests and questionnaires to measure creativity and environmental awareness. The data analysis technique used one-party t-test. The results showed that ethnoscience-based integrated science learning can foster environmental awareness and student creativity and can improve environmental care and student creativity in ethnoscience-based integrated science learning, in the medium category. This research is very useful in showing how science works in society, and it is more applicable.